1994
DOI: 10.1007/bf01435250
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the tobaccoTnt1 retrotransposon

Abstract: Retroelements represent by far the largest and most widespread class of mobile genetic elements. Representative of several classes of retrotransposons have been characterized in a broad range of plant species, but only a few of them have been shown to be active. Among these, the tobacco Tnt1 retrotransposon has been isolated after insertion mutagenesis and is one of the very few to be transcriptionally active. Tnt1 expression is strongly regulated in a tissue-specific and developmental manner. Moreover, Tnt1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…2). This appears to be a general feature in retroelement expression since root-specific expression has also been described for the Tnt1 retrotransposon (Pouteau et al, 1991;Grandbastien et al, 1994), while others such as BARE-1 from barley and PREM-2 from maize are specifically transcribed in leaves and microspores, respectively (Suoniemi et al, 1996a(Suoniemi et al, , 1996bTurcich et al, 1996).…”
Section: Transcriptional Induction Of Tlc1 In Response To Stress Condmentioning
confidence: 76%
See 1 more Smart Citation
“…2). This appears to be a general feature in retroelement expression since root-specific expression has also been described for the Tnt1 retrotransposon (Pouteau et al, 1991;Grandbastien et al, 1994), while others such as BARE-1 from barley and PREM-2 from maize are specifically transcribed in leaves and microspores, respectively (Suoniemi et al, 1996a(Suoniemi et al, , 1996bTurcich et al, 1996).…”
Section: Transcriptional Induction Of Tlc1 In Response To Stress Condmentioning
confidence: 76%
“…Transcription is a key event in duplicative transposition and is involved in both the production of genomic RNA used as template for RT and the production of mRNA species required for the synthesis of proteins necessary for transposition . In plant retrotransposons, the transcription step appears to be a tissue-specific and a developmentally regulated process (Pouteau et al, 1991;Grandbastien et al, 1994;Kumar and Bennetzen, 1999). Expression of the Tnt1 and Tto1 elements of tobacco (Pouteau et al, 1991Hirochika, 1993;Moreau-Mhiri et al, 1996;Grandbastien et al, 1997) and the Tos elements of rice (Hirochika et al, 1996) was shown to be greatly increased by stress conditions, including protoplast isolation, cell culture, or pathogen attack (for review, see Wessler, 1996;Kumar and Bennetzen, 1999).…”
mentioning
confidence: 99%
“…Thus, the absence of germinal transposition events in the progeny of transgenic plants carrying Tnt1 and the early occurrence of transposed copies obtained in transgenic lettuce after in vitro regeneration and transformation are in keeping with the element's transcription pattern. Tnt1 transcription has previously been shown to be strongly regulated and induced by different biotic or abiotic stress factors, such as treatment with herbicides, microbial elicitors, wounding, and 2,4-dichlorophenoxyacetic acid (Pouteau et al, 1991Grandbastien et al, 1994;Pauls et al, 1994;Moreau-Mhiri et al, 1996;Mhiri et al, 1999) and during in vitro transformation of Arabidopsis (Courtial et al, 2001) and Medicago (d'Erfurth et al, 2003). Thus, transcriptional regulation of Tnt1 (at least in intact plants and during in vitro culture) appears to be conserved in the heterologous host lettuce.…”
Section: Discussionmentioning
confidence: 99%
“…Our work demonstrated that transposition occurred in 40% of the R108 regenerated plants from a small mutant collection, with an average new copy number of one element per plant in the total collection, indicating a mild activity of the element in this background during tissue culture. The stability of the MERE1 retroelement copy number in M. truncatula (and L. japonicus) might result, as for Tnt1 (Grandbastien et al, 1994), from a long coevolution of this particular family of retroelements with its host organism. Interestingly, this element was also found active in the M. truncatula Jemalong 2HA line used to generate the Medicago Tnt1 insertion mutant collection (www.eugrainlegume.…”
Section: Mere1 Is An Active Retroelement In M Truncatulamentioning
confidence: 99%